Intramolecular cyclization reactions in haloalkyl-cobalt complexes with macrocyclic equatorial ligands - Dreos, Renata (Array, 2009)
Summary: Organocobalt complexes containing axial haloalkyl groups afford metallacycles of different size by N or O alkylation of the macrocyclic equatorial ligands. The reaction mechanism involves the intra-molecular nucleophilic attack of a negatively charged atom of the equatorial ligand on the axial XCH2 haloalkyl group with simultaneous detachment of a halide ion, X−. In imino/oxime and amino/oxime derivatives, the generation of the negatively charged nitrogen requires the abstraction of a proton and the reaction occurs only in alkaline medium. In bis(dimethylglioximato) and Schiff base complexes, a negatively charged oxygen is present in the equatorial ligand and the reaction occurs even in neutral medium. Three-, six- and seven- membered metallacycles are obtained, with the common feature that the Co–C bond is shorter and more resistant toward homolysis than in parent complexes or in closely related derivatives